2017
DOI: 10.1177/0263617416686798
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and spectroscopic studies on β-cyclodextrin functionalized ionic liquid as chiral stationary phase: Enantioseparation of NSAIDs

Abstract: Recently, we reported a new chiral stationary phase prepared using b-cyclodextrin functionalized with aromatic ionic liquid which is aimed to enhance the performance of enantioseparation of flavonoids and b-blockers. In this paper, the characteristics and performance of previously prepared chiral stationary phase denoted as b-CD-BIMOTs were compared with the newly synthesized chiral stationary phase denoted as b-CD-DIMOTs. b-CD-DIMOTs were prepared by functionalization of b-cyclodextrin with aliphatic ionic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Rahim et al reported new chiral stationary phases, (β-CD-BIMOTs, β-CD-DIMOTs), prepared using aromatic ionic liquids functionalized with β-cyclodextrin, designed to enhance the enantiomeric separation of flavonoids and β-blockers. They compared the enantiomeric separation ability of non-steroidal anti-inflammatory drugs (ibuprofen, indoprofen, ketoprofen, and fenoprofen) between β-CD-BIMOTs and β-CD-DIMOTs stationary phases with the native β-CD stationary phase, demonstrating that β-CD-BIMOTs stationary phases have better separation abilities due to the superposition of hydrogen bonding, hydrophobic, and also p–p interactions [ 56 ].…”
Section: Ionic Liquids In Pharmaceutical Applicationsmentioning
confidence: 99%
“…Rahim et al reported new chiral stationary phases, (β-CD-BIMOTs, β-CD-DIMOTs), prepared using aromatic ionic liquids functionalized with β-cyclodextrin, designed to enhance the enantiomeric separation of flavonoids and β-blockers. They compared the enantiomeric separation ability of non-steroidal anti-inflammatory drugs (ibuprofen, indoprofen, ketoprofen, and fenoprofen) between β-CD-BIMOTs and β-CD-DIMOTs stationary phases with the native β-CD stationary phase, demonstrating that β-CD-BIMOTs stationary phases have better separation abilities due to the superposition of hydrogen bonding, hydrophobic, and also p–p interactions [ 56 ].…”
Section: Ionic Liquids In Pharmaceutical Applicationsmentioning
confidence: 99%
“…This review focuses primarily on the determination of pharmaceuticals in biological and environmental samples, so it should be strongly highlighted here that the number of publications related to the determination of such analytes on IL columns by LC is negligible. Two such articles were published by Rahim et al [163,164]. They prepared a stationary phase based on β-cyclodextrin and 3-benzylimidazolium tosylate as ILs for the enantioseparation of β-blockers and NSAIDs.…”
Section: Ionic Liquid Stationary Phasesmentioning
confidence: 99%
“…In the majority of the reported cases, the IL is covalently bound to the CD rim. As an example, ionic liquid grafted by the nitrogen atom of imidazolium on the primary face of β-cyclodextrin was immobilized on modi ed silica and used as chiral support in high-performance liquid chromatography (Rahim et al 2016a;Rahim et al 2016b), in capillary gas chromatography (Zhang et al 2011) or in capillary electrophoresis (Zhou et al 2017) (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…1a). The presence of the ionic species improved the enantioseparation of β-blockers and avonoids thanks to the formation of intermolecular inclusion complex but also owing to an original π-π interaction between the aromatic guest and the imidazolium cycle (Rahim et al 2016a;Rahim et al 2016b). The original electrochemical properties of ionic liquids and the high supramolecular recognition properties of cyclodextrins were also tested on metallic supports such as Pt-Co (Zhao et al 2010), graphite (Mohamad et al 2015;Rasdi et al 2016), Fe 3 O 4 (Sinniah et al 2015, Bahadorikhalili et al 2019, Au-graphene oxide (Li et al 2016) producing new nanoparticles and hybrid nanomaterials (Fig.…”
Section: Introductionmentioning
confidence: 99%